EMERGING MRI TECHNIQUES IN KIDNEY CANCER: DIFFUSIONWEIGHTED IMAGING, SPECTROSCOPY, AND BEYOND (World Bulletin of Public Health, 2024)
Kidney cancer, especially renal cell carcinoma, is highlighted as a significant contributor to cancer incidence. Advanced volumetric visualization techniques enable the detection of small renal tumors, facilitate prognostic assessments of tumor progression, and support organ-preserving surgical interventions
Keywords: renal cell carcinoma; radiology